Simultaneously reinforcing and toughening epoxy network with a novel hyperbranched polysiloxane modifier. Issue 23 (23rd February 2018) - Liu, Hanchao; Gao, Xiaoxiao; Deng, Bo; Huang, Guangsu
ABSTRACT: A novel hyperbranched polysiloxane (HBPSi) was prepared and cured into an epoxy–aromatic amine network without phase separation. A moderate content of HBPSi increased the crosslinking density of the crosslinking network because of the active amino groups on the HBPSi. Meanwhile, the secondary amine on the HBPSi molecules improved the homogeneity of the epoxy network. At a 5 wt % HBPSi content, the tensile strength, tensile modulus, and flexural modulus were enhanced by 17.6%, 13.7%, and 17.5%, respectively, compared with those of the neat epoxy resin. Meanwhile, the elongation at break and impact strength were 63.3% and 49.1% higher than those of the neat epoxy resin, respectively. HBPSi also significantly increased the char yield of the material and decreased the thermal weight loss rate; this indicated an improved thermal stability. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46340. Abstract :